"La Manada" in the digital sphere: coping with a sexual aggression case through Twitter. Issue 7 (2nd October 2020) - Idoiaga Mondragon, Nahia; Gil de Montes Echaide, Lorena; Asla Alcibar, Nagore; Larrañaga Eguileor, Maider
ABSTRACT: The gang rape known as the "La Manada" case has had an unprecedented social impact in Spain. This research investigates how this case has been dealt with through Twitter by a collective symbolic coping process (Social Representation Theory). Discourse on Twitter was analyzed at two key points in time: the announcement of the judgment and the aggressors' release from prison. In total 6, 592 tweets with the hashtag #lamanada were selected and their content was analyzed by lexical analysis using Iramuteq software. The results reveal both an awareness phase about the issue along with a divergence phase that saw the emergence of various interpretations about this case, which were confronted. In this divergence phase, feminist discourses took on great significance, expressing anger, calling for social mobilizations, criticizing the victim blaming and creating a dialogue against rape culture. However, the anti-feminist and sexist discourses were also present in this space. It is concluded that discourses on Twitter are a symptom of a shift in mentality whilst at the same time serve as an active constructor of this changed knowledge. Thus, the feminist movement should continue to take this into account in order to converge and normalize the discourse against rape culture.